Emergence of appetite and circadian rhythmicity in Atlantic salmon brain transcriptome from endogenous to exogenous feeding - Sissel Norland; Mariann Eilertsen; Ana S. Gomes; David W. P. Dolan; Rita Karlsen; Ivar Rønnestad; Jon Vidar Helvik (PLoS ONE, 2026)
Successful transition from endogenous yolk utilization to exogenous feeding is critical for survival in fish larvae, yet the changes in the brain during this transition remain incompletely described. In this study, whole-brain RNA sequencing was used to investigate transcriptomic changes over 48 h during endogenous yolk utilization (720 day degrees (dd)) and after the onset of exogenous feeding (920 dd) in Atlantic salmon ( Salmo salar ), focusing on appetite-related genes. Key components of appetite control, including melanocortin system and nutrient-sensing pathway, were present at 720 dd and elevated levels were observed at 920 dd. Before onset of first feeding, 16 appetite-related genes displayed a significant cyclic profile, where most had a periodicity of 20 h or 28 h. Following the transition from endogenous to exogenous feeding, the majority of significantly cyclic appetite-related genes exhibited a periodicity of 24 h, suggesting the establishment of circadian regulation associated with energy homeostasis. These results indicate that a pre-programmed expression of appetite and energy-related genes occurs in the brain before the yolk is fully utilized. Two weeks into the first feeding period (920 dd), the whole-brain transcriptome showed better responsiveness to feeding, but a fully developed satiety system remained underdeveloped. Additionally, characterization of hypothalamic melanocortin neuropeptides distribution during early salmon development revealed a spatial organization distinct from that reported in later life stages.